1994
DOI: 10.1590/s0004-282x1994000400018
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea treatment with dental appliance

Abstract: The case of a 40-year-old male patient with obstructive sleep apnea syndrome (OSAS) is reported, with emphasis on treatment with a dental appliance. This therapeutic approach, which has been focused on recent research, has as its objective, the posturing of the mandibule and, consequently, the tongue more anteriorly, thus in turn leading to an increase in the posterior oropharyngeal airway space (PAS). Cephalometry contributed determining in this case whereby enlargement limits were observed in the PAS with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…At the pathophysiological level, OSAS is based on a partial or complete obstruction of the airways during sleep, which derives from a collapse of the tissues that form the PAS (posterior airway space). This collapse can occur at different points: affecting the soft palate (the most common), from the walls of the pharynx, the base of the tongue, or the epiglottis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the pathophysiological level, OSAS is based on a partial or complete obstruction of the airways during sleep, which derives from a collapse of the tissues that form the PAS (posterior airway space). This collapse can occur at different points: affecting the soft palate (the most common), from the walls of the pharynx, the base of the tongue, or the epiglottis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These oral appliances, to be worn during sleep, increase the upper-airway space through a mechanical action via two different strategies: to lead the tongue into a more advanced position (tongue-retaining devices) and to determine mandibular advancement (mandibular advancement device or MAD). These devices are well tolerated by patients, easy to use, noninvasive, and removable, with mild and, overall, acceptable side effects [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…OSAS disorganizes the relational life of the patient, affecting his/her ability to maintain an adequate social life and negatively influencing his/her quality of life 1 . Intraoral devices have been developed as an alternative treatment for OSAS, and some studies have shown improvement in the quality of life of patients who systematically use an intraoral device that positions the mandible anteriorly and increases the dimensions of the collapsible region of the airways [6][7][8] . In addition to the cited mandibular repositioners, other treatments available include continuous positive airway pressure (CPAP) -the standard treatment for severe apneas -and surgical procedures which, however, have not yet been evaluated in high quality clinical studies 9,10 .…”
mentioning
confidence: 99%